Effect of sodium nitroprusside treatment on shikimate and phenylpropanoid pathways of apple fruit. (30th August 2019) - Ge, Yonghong; Chen, Yanru; Li, Canying; Zhao, Jirong; Wei, Meilin; Li, Xihong; Yang, Shuqi; Mi, Yitian
Highlights: SNP induced MdDHQS, MdSKDH, MdSK and MdEPSPS expressions. SNP promoted shikimic acid, tryptophan, tyrosine and phenylalanine accumulation. SNP activated the phenylpropanoid pathway. Phenylpropanoid pathway is closely related to shikimate pathway in apples. Abstract: Blue mould caused by Penicillium expansum is one of the important diseases of apple fruit during storage. Phenylpropanoid pathway is an important induction mechanism that can utilize downstream metabolites of shikimate pathway to synthesize a series of secondary metabolites. Apple fruit (cv. Fuji) were treated with sodium nitroprusside (SNP) to study its effect on blue mould, shikimate and phenylpropanoid pathways. The results showed that 1.0 mmol L −1 SNP significantly inhibited lesion development of apple fruit inoculated with P. expansum . The results also indicated that SNP enhanced MdDHQS, MdSKDH, MdSK and MdEPSPS genes expressions, increased shikimic acid, tryptophan, tyrosine and phenylalanine contents in apple fruit. The activities of phenylalanine ammonialyase, 4-coumarate: coenzyme A, ligase, cinnamate 4-hydroxylase, lignin, total phenolic compounds and flavonoids contents in apple fruit were also increased by SNP treatment. These results suggest that SNP might modulate shikimate and phenylpropanoid pathways to enhance disease resistance of apple fruit.